MEASURING HUMAN RESOURCE MANAGEMENT MATURITY LEVEL USING PEOPLE CAPABILITY MATURITY MODEL AT INSTITUT TEKNOLOGI BANDUNG - Rifani, Diantika
Institut Teknologi Bandung (ITB) is a technical school in Indonesia. To fulfill ITB’s vision and mission, its people capability, including both its academic and non-academic staff, plays a big role in ensuring ITB’s success. With its people capability possessing a big role and a massive amount of staff—more than 2.500 staff running its 51 academic majors, ITB formed a technical implementation unit which focuses on human resource and organizational development, called UPT PMO ITB (Unit Pelaksana Teknis Pengembangan Manusia dan Organisasi Institut Teknologi Bandung). UPT PMO ITB is responsible to design human resource development program. In order to fulfill that, People Capability Maturity Model is used here as a reference framework. In this paper, a specific measuring model for ITB was developed first, to ensure that the measuring tool is relevant to human resource development process in ITB, then the measuring tool is used to measure the maturity level of human resource development in ITB, and last, improvement recommendation is made according to the maturity measurement result. The specific measuring model was developed through Delphi method aided with a form to be filled by the panelists, resulting in all model statements accepted as relevant, and a list of specific artefacts relevant to ITB related to each statements. Next, the developed measuring model is used at ITB, with the result showing that ITB’s people capability maturity level, specifically on the human resource development aspect, is still on the lowest level which is level 1 (initial). Based on the result, an improvement framework is made, that included assigning an individual to be responsible on training and development in each unit, allocating reserved time for training and development, identificating critical skills for each job, developing training plan in each unit, holding timely training, holding development discussion periodically with each individual, and assigning a responsible individual(s) to verify that training and development activities are conducted according to the documented policies and address non-compliance.